2016
DOI: 10.2807/1560-7917.es.2016.21.11.30167
|View full text |Cite
|
Sign up to set email alerts
|

Measles outbreak in a refugee settlement in Calais, France: January to February 2016

Abstract: We report a measles outbreak in a refugee settlement in Calais, France, between 5 January and 11 February 2016. In total, 13 confirmed measles cases were identified among migrants, healthcare workers in hospital and volunteers working on site. A large scale vaccination campaign was carried out in the settlement within two weeks of outbreak notification. In total, 60% of the estimated target population of 3,500 refugees was vaccinated during the week-long campaign.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
41
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 3 publications
0
41
1
Order By: Relevance
“…As thousands of asylum seekers from countries with disrupted vaccination programs have entered Europe and Finland during the previous year, diseases that have been rare or nonexistent in Finland may reappear with this trend. Examples of this have already been seen in Europe as Germany and France have experienced measles epidemics among the asylum seekers [5,14], and polio cases have been reported during the war in Syria [15]. …”
mentioning
confidence: 89%
See 1 more Smart Citation
“…As thousands of asylum seekers from countries with disrupted vaccination programs have entered Europe and Finland during the previous year, diseases that have been rare or nonexistent in Finland may reappear with this trend. Examples of this have already been seen in Europe as Germany and France have experienced measles epidemics among the asylum seekers [5,14], and polio cases have been reported during the war in Syria [15]. …”
mentioning
confidence: 89%
“…Numerous measles outbreaks have recently occurred in Europe [4,5]. The proportion of HCWs with suboptimal levels of antibodies against measles has varied from 1.6% to 19% in European studies done in this century [6].…”
mentioning
confidence: 99%
“…It was demonstrated that diseases that can be prevented by vaccination cause flare-ups in reception and holding centers [39,42,43,44,45,46,47,48]. Outbreaks are generally more severe in refugee camps [48].…”
Section: Health Problems Facing Refugeesmentioning
confidence: 99%
“…Children and the elderly are undoubtedly particularly vulnerable [50,51,52]. In addition, overcrowding in holding/detention centers or refugee camps may contribute to the rapid spread of communicable diseases, such as influenza, varicella, tuberculosis, measles, and meningococcal disease [16,17,39,42,43,44,45,46,47,48,49]. It is predicted that the complication rates for influenza in this setting will be double those in the general population [53].…”
Section: Health Problems Facing Refugeesmentioning
confidence: 99%
“…Thus, the initial contamination might have come from a non-immunised European volunteer [3] and the refugee settlement with vulnerable individuals acted as an 'epidemiological amplifier' of this communicable infection. However, that was a small outbreak with limited number of cases.…”
mentioning
confidence: 99%